Gênese de concentrações densamente fossilíferas do Eoceno médio, formação man aike, bacia foreland Magallanes (Patagônia Chilena) - Müller, Eduardo Guareschi (Universidade do Vale do Rio dos Sinos, 2021)
In the Middle Eocene marine deposits of the Magallanes region, Ultima Esperanza Province (Chile), there are fossiliferous concentrations associated with shallow marine siliciclastic deposits. During this period, climatic oscillations and global changes in marine circulation occurred recording variations in the relative sea level in the southern region of the South American Plate and in Antarctica. On the northwestern edge of the Magallanes Basin, in the locality of El Puesto (Rio de Las Chinas Valley, Patagonia Chilena), outcrop siliciclastic coarse-grained deposits, interspersed with dense fossiliferous concentrations representing part of the Middle Eocene deposition. Seeking to improve paleoenvironmental interpretations, this study presents a multi-proxy characterization, based on facies analysis, taphonomy and FRX (X-Ray Fluorescence) analysis, in order to understand the genesis of densely fossiliferous concentrations of the Man Aike Formation. The base of the Man Aike Formation presents as transgressive shoreface deposits. The results corroborate previous interpretations of a shallow marine deposition from an upper shoreface transitioning to a lower shoreface, under the influence of high energy processes with controlled deposition by currents and waves. The fossiliferous concentrations indicate a deposition under the action of good weather waves and storm waves, related to proximal and distal storms. Proximal deposits are interpreted as lag concentrations. Another record concerns hiatal deposits with formation of event concentrations (fossil associations of the ecological sense type) and episodic deposits related to debris flows. The records of terrigenous/Ca, Al/Ca, Ti/Al and Sr/Ca ratios suggest a transgressive trend towards the top of the section. The sedimentary piling patterns and geochemical data obtained are related to climatic events that occurred in the Eocene, which caused a consequent relative rise in sea level starting at approximately 45 Ma.
Keywords: Bacia de Magallanes; Depósito marinho; Eoceno médio; Fossilíferas; Magallanes basin; Marine deposit; Middle eocene; Fossils; ACCNPQ::Ciências Exatas e da Terra::Geologia